Gypsum incubation tests to evaluate its potential effects on acidic soils of Colombia - Jorge Enrique Cuervo-Alzate; Nelson Walter Osorio (Revista Facultad Nacional de Agronomía Medellín, 2020)
Tropical soils are characterized by acidity and poor plant nutrient availability, limiting their agricultural productivity. These soils are commonly amended with lime, but its low solubility impairs its effectiveness to enhance soil fertility. The use of gypsum has gained attention among farmers due to its higher solubility and mobility in the soil, local accessibility, and low price. Therefore, this study was conducted to determine the effects of Agricultural Gypsum (AG) addition on ten Colombian acid soils that had poor fertility and contrasting their physical and chemical characteristics. Surface (0-20 cm) soil samples were air-dried, sieved (<2 mm), and transferred into plastic vases, 40 g (dry base) per vase. Increasing rates of gypsum were added by duplicate: 0.0, 0.25, 0.5, 1.0, 2.0, 4.0, 8.0, and 16.0 g kg-1. Then, the soils were incubated for two weeks and watered to maintain 50% of their maximum water holding capacity. Soil pH, Al+3, Ca+2, Mg+2, K+, S-SO4-2, and P-H2PO4-2 were measured using standard methods. The results showed that AG addition significantly (P<0.05) increased soil exchangeable Ca+2-K+, Ca+2 saturation, S-SO4-2 concentration, and exchangeable Al+3, particularly with doses above 4.0 g kg-1. In contrast, soil Al+3 saturation, P-H2PO4-2 and pH significantly decreased as the AG doses increased, while soil exchangeable Mg+2 levels were not significantly affected. The use of gypsum incubation tests could be promissory for its effects on soil amelioration associated mainly to increase soil exchangeable Ca2+ and S-SO 42- and to decrease Al3+ saturation.